Grid-connected Photovoltaic Power Systems and Power Quality Improvement Based on Active Power Filter - Brahim Berbaoui; Samira Dib; Rachid Dehini (Institute of Advanced Engineering and Science, 2014)
This paper presents a Parallel Active Power Filter (PAPF) using Photovoltaic cells Energy to feed linear or nonlinear loads with current perturbations compensation and the excess of the energy is injected into the mains. As a result of using instantaneous p-q theory as a control scheme, the multi-function operation such as harmonic elimination, reactive power control and uninterruptible power supply will be achieved. The system consisting of Photovoltaic cells, connected to a diode rectifier feeding a parallel active power filter is simulated in MATLAB/SIMULINK environment. The simulation results prove the efficiency of using the proposed method for Photovoltaic cells energy injection and power quality improvement in the grid power system.